PROJECT BASED LEARNING DESIGN DEVELOPMENT OF FOOD ADDITIONAL INGREDIENTS GREEN CHEMISTRY APPROACH TO SUPPORT SCIENTIFIC LITERACY OF CULINARY VOCATIONAL HIGH SCHOOL STUDENTS: AN INTRODUCTORY STUDY - Izza Nabilatunnisa; Hernani Hernani (Universitas Lambung Mangkurat, 2024)
This research aims to determine the need for PjBL learning design and learning tools that use a green chemistry approach to food additives to support the scientific literacy of culinary vocational school students. The type of research used is evaluation research using needs assessment to describe the need for learning designs that can be used to support the learning outcomes of culinary vocational school students. Data was collected in the form of a 12 question survey via Google-form with a total of six culinary vocational school teachers using purposive sampling. The results of the research found that (1) all vocational school teachers in culinary field already understand the specifics of the independent curriculum currently used and are familiar with the scientific literacy competencies listed in the general achievements; (2) 4 out of 6 teachers understand the concept of Cleanliness Health Safety Environmental Sustainability (CHSE), 5 out of 6 teachers understand green chemistry and all teachers state that there is a relationship between these two concepts; (3) 5 out of 6 teachers have implemented PjBL and; (4) all teachers stated that there was a lack of learning resources available to support scientific literacy. The results of this research show that culinary vocational school teachers need a PjBL learning design with a green chemistry approach along with learning tools to support the scientific literacy of culinary vocational school students